Costs and benefits of diagnostic testing: four ways to improve patient care by purposive use of in vitro diagnostics (Swiss Medical Weekly, 2017)
Scientific advances and innovative targeted drugs, especially biologics, have revolutionised the treatment of many diseases. In oncology in particular, previously acute or lethal conditions have come to be considered chronic as new treatments have led to longer life expectancies and a lower rate of years lived with disability. These advances, however, come with rising costs in a resource-constrained environment. To achieve cost containment, reimbursement for in-vitro diagnostics (IVDs) is increasingly coming under pressure because they are perceived as a cost factor rather than as a tool to reduce expenditure in the long term. In this conceptual paper, we propose four possible interventions from an industry perspective that may contribute to increase effectiveness of IVD use to counteract increasing healthcare expenditures. These are: (1) fostering prevention, screening, early diagnosis and therapy; promoting (2) comprehensive and (3) stratified disease management; and (4) using targeted treatment alongside companion diagnostics. We conclude that the implementation of policies that promote a fee-for-outcome model rather than fee-for-service reimbursement can support sustainable healthcare.